2007
DOI: 10.1038/sj.ijo.0803548
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and metabolic effects of topiramate in overweight and obese type 2 diabetic patients: randomized double-blind placebo-controlled trial

Abstract: Objective: To examine the metabolic effects and body composition changes after topiramate treatment of obese type 2 diabetic patients (DM2) for 11 months. Design and subjects: Thirty-eight DM2 on diet or sulfonylurea treatment participated in this randomized double-blind placebocontrolled trial. Thirteen placebo-treated and nine topiramate-treated patients completed the trial. Patients were randomized to treatment with topiramate 96 mg b.i.d. or placebo (6-week run-in phase, 2-months titration phase, 9-months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 23 publications
3
28
1
1
Order By: Relevance
“…In addition, Li et al (28) observed no differences in HOMA-IR after 6 months of topiramate treatment in children with epilepsy (median dosage 2.15 mg/kg/day). In a study of Eliasson et al (29) in T2DM patients, an improvement in insulin-stimulated glucose disposal (using a hyperinsulinemic euglycemic clamp) could not be detected after 11 months of topiramate treatment (192 mg/day), despite a significant decrease in body weight, fasting plasma glucose, and HbA1c. A trend in enhanced hepatic insulin sensitivity was observed, but this difference did not reach statistical significance, perhaps because of the limited sample size and the relatively high-insulin infusion rate (1 mU/kg per min), which might be expected to suppress hepatic glucose production almost completely.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Li et al (28) observed no differences in HOMA-IR after 6 months of topiramate treatment in children with epilepsy (median dosage 2.15 mg/kg/day). In a study of Eliasson et al (29) in T2DM patients, an improvement in insulin-stimulated glucose disposal (using a hyperinsulinemic euglycemic clamp) could not be detected after 11 months of topiramate treatment (192 mg/day), despite a significant decrease in body weight, fasting plasma glucose, and HbA1c. A trend in enhanced hepatic insulin sensitivity was observed, but this difference did not reach statistical significance, perhaps because of the limited sample size and the relatively high-insulin infusion rate (1 mU/kg per min), which might be expected to suppress hepatic glucose production almost completely.…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated that these chronic oxytocin effects result from 1) maintenance of energy expenditure at preintervention levels despite ongoing weight loss, 2) a robust reduction in respiratory quotient, consistent with increased fat oxidation, and 3) an enhanced satiety response to CCK-8 and associated reduction of meal size. In contrast to other anti-obesogenic therapies, including melanocortin receptor ligands [MTII (72), BIM-22493 (46)], topiramate (27), and the GLP-1 receptor agonist, liraglutide (50), which reduce both fat mass and lean mass, oxytocin is one of the few hormones that we are aware of [aside from leptin (36,41,69)] that protects against the loss in lean mass and selectively reduces fat mass, thus highlighting its translational potential. Combined with our evidence that chronic subcutaneous infusions of oxytocin are sufficient to reduce body weight gain in animals maintained on a HFD at a dose that does not appear to elicit aversive behavioral responses (e.g., nausea or malaise), these findings identify oxytocin as a viable agent for obesity prevention and treatment.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…This finding is concordant with the recent data suggesting meaningful improvements in glycemic control parameters after topiramate treatment. 10,[16][17][18][19] Although reduction of waist circumference can be associated with weight reduction, there is no unequivocal report regarding whether topiramate's effects on glycemic parameters are dependent on its weight loss effects. Therefore, contrary to the reduction in waist circumference, the improvement in insulin resistance may not be directly attributed to the weight loss effects of topiramate, according to the available data.…”
Section: Discussionmentioning
confidence: 99%